Description of a new species of the Central Palaearctic genus Margelana Staudinger (Lepidoptera: Noctuidae) from northeastern Iran - Fibiger, Michael; Zahiri, Reza; Kononenko, Vladimir S. (Zootaxa, 2007)
The genus Margelana Staudinger, 1888 is a member of the tribe Apameini in the subfamily Xyleninae sensu Fibiger & Lafontaine 2005. The genus comprises three superficially similar species, all occurring from the Middle East to the Central Palaearctic region: Margelana versicolor (Staudinger, 1888), M. flavidior F. Wagner, 1931 (with its subspecies M. flavidior ochrea Brandt, 1941) and M. brunnea, sp. n. The habitat of all three species is dry rocky steppe with herbaceous vegetation and scattered bushes. Adults and male and female genitalia of all three species of Margelana are described, compared and illustrated. All three species occur in Iran.